ANALISIS PENGAWASAN PERSEDIAAN BAHAN BAKU YANG EFEKTIF GUNA MENDUKUNG KELANCARAN PROSES PRODUKSI DI UPSOLUTE COFFEE CILACAP - Herni Utami Rahmawati; Nurul Hasanah; Mutiasari (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
Effective Raw Material Supply Monitoring Analysis to Support Smooth Production Process at Upsolute Coffee Cilacap". Problem 1. Whether the implementation of supervision of raw material supplies to support the production process carried out by Upsolute Coffee has not been efficient; 2. Is there a difference between the cost of procurement of raw materials in fact and the economy. Control of raw material supplies needs to be done properly in order to be available in the right amount and time so that the production process can run smoothly and the cost of raw material supplies can be suppressed. Research Objectives 1. Analyzing the efficiency of the supervision of raw material supplies to support the production process carried out by Upsolute Coffee; 2. Analyze the difference between the actual cost of procurement of raw materials and the economical ones. This research is a quantitative descriptive analysis study. Data Analysis Techniques using the EOQ, TIC, ROP, and Savety Stock methods. EOQ is the number or size of orders owned, the amount of order fees, and the minimum per-year inventory costs (Assauri, 2008). ROP is a point or limit to the amount of inventory available at a time when the booking must be held again. Safety stock is an additional supply held to maintain the possibility of material shortages. The implementation of supervision of raw material supplies to support the production process carried out by Upsolute Coffee has not been efficient. There is a difference between the actual cost of procurement of raw materials and the cost of economical raw materials.